Respostas

2013-12-10T20:46:29-02:00
Lim    -1                                 (x²+2x-3/4x-3) 
x→

lim    -1                               (-1)^2 + 2 * (-1) - 3
 x→                                       4 * (-1) - 3

lim    -1                               1+ (-2) - 3
 x→                                       (-4) - 3

lim    -1                                - 4
 x→                                     - 7

Resposta:O limite de -1 com x tendendo a -1 =                                 - 4
                                                                                                      7